Integração intersetorial no projeto re-ciclo de resíduos sólidos urbanos em Fortaleza - Lucas, Airton Douglas de Andrade (2024)
The proposed theme expresses academic relevance by exploring the nuances of integration between the public, private and non-profit sectors, investigating specific integration mechanisms (cooperation, coordination and collaboration) adopted by the model proposed by Keast, Brown and Mandell (2012). Integration plays an increasingly representative role in the formulation and practice of public policies in many territories. Based on the differentiated panorama of the composition of relationships between population and government, integration mechanisms provide new work models that guarantee positive results for social issues supposedly with long-term solutions. The general objective of this study is to investigate the intersectoral integration of the Re-ciclo Project using the 3C's typology (cooperation, coordination and collaboration) proposed by Keast, Brown and Mandell (2012). This is a case study, with an descriptive and qualitative scope, along the lines of field research carried out through interviews with managers of municipal public organizations, private companies and the third sector. Documentary research was also carried out on projects and the hiring process of private companies on the transparency disclosure portals of Public Authorities and Control Bodies. The research results indicate that the intersectoral integration of the Re-ciclo Project occurs through planned actions of cooperation, coordination and collaboration between the organizers, representatives of the three sectors. Regarding the stages of cooperation, the research results point to dialogue and the exchange of information between the actors representing the Re-ciclo Project. In terms of coordination, the research results pointed to average relationships and a need for greater planning and exchange of information, especially with waste picker associations. In the collaboration stage, all actors highlighted a synergy to leverage the Re-ciclo Project using all intersectoral integration mechanisms more intensively. In short, it is considered that the intersectoral integration of the Re-ciclo Project, according to the model by Keast, Brown and Mandell (2012), presented a positive framework for the development and advancement of cooperation, cooperation and collaboration practices, providing positive integration and sustainable among the representatives involved. The economic benefits include the generation of jobs, improved income for the workers involved and the supply of low-cost recyclable material to industry and the reduction of municipal expenses. Regarding social benefits, the project makes contributions to public health and the sanitation system, in addition to promoting the quality of life of waste pickers, offering them better and more regular working conditions and social reintegration. As for environmental benefits, recycling collection from the Re-ciclo Project is transformed into raw material, thus preserving the environment and promoting a cleaner city.